(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is determination of the prevalence and clinical significance of random findings detected in digital panoramic images of complete edentulism patients, applied for prosthetic treatment.Material and Methods: Of the 382 images, 189 digital panoramic images (49.5%) matching the study criteria were included in the study. The positive findings were evaluated, such as impacted teeth, residual roots, radiolucent lesions, radiopaque (RO) lesions, foreign bodies, atrophic crest, soft tissue calcifications (STCs), maxillary sinus opacities, Stafne bone defects, stylohyoid ligament ossifications, and laryngeal cartilage calcifications. The findings were analyzed in different age groups and evaluated with descriptive analysis.Results: Images of 100 male (53%) and 89 female (47%) patients with a mean age of 64.2±9.6 were examined. It was found that 80% (n=151) of the patients were delivered conventional complete dentures, 20% (n=38) of them were delivered complete dentures in the upper jaw, and two implant-retained overdentures in the lower jaw. The detected positive radiographic findings were 94.7% (n=179); 48.7% (n=87) were in female and 51.3% (n=92) were in male. The most common positive findings were maxillary (50.7%) and mandibular (28.4%) crest atrophies, followed by maxillary sinus opacities (25.9%), and STCs in tonsilloliths region (18.5%). In all age groups, the most common positive finding was maxillary crest atrophy.Conclusion: The results of this study showed that the rate of positive findings detected in digital panoramic images of completely edentulous patients was high. Routine use and careful examination of panoramic images are essential for patients with complete edentulism.